Increased Terrigenous Supply to the Pelagic Panthalassa Superocean Across the Carnian Pluvial Episode: A Possible Link With Extensive Aridification in the Pangean Interior - Cho, Tenichi; Ikeda, Masayuki; Ohta, Tohru (Frontiers in Earth Science, 2022)
In the Late Triassic, a global environmental change called the Carnian Pluvial Episode (CPE) emerged, causing major biological turnover. The CPE has been recognized by siliciclastic input to sedimentary basins, multiple carbon isotope perturbations, and climate proxies for humidification. The CPE is considered to have been associated with increased atmospheric pCO2 from eruptions of large igneous provinces. However, the nature of this global environmental perturbation on the continents is still not well understood. Here we present a geochemical analysis of a pelagic deep-sea bedded chert sequence across the CPE in the Jurassic accretionary complex of Mino terrane, central Japan. Fluctuations in terrigenous material supply were reconstructed using Principal Component Analysis of major element compositions. The first principal component positively correlates with elements enriched in clay minerals such as Al2O3, whereas it negatively correlates with CaO, P2O5, and MnO, derived from apatite and manganese. A sudden increase in terrigenous supply was detected around the Julian/Tuvalian boundary, suggesting that CPE-related siliciclastic input also occurred in the abyssal plain environment. The terrigenous supply returned to the pre-CPE state in the Tuvalian. Since the terrigenous material supplied to the abyssal plain is thought to be derived from eolian dust blown from continental arid regions, the increasing terrigenous supply detected in the pelagic deep-sea chert succession may indicate extensive aridification. This result seems to conflict with the common view of the CPE as a humidification event. This contradiction possibly suggests that the extensive aridification occurred within the interior of the supercontinent Pangea, while hydrological circulation enhanced on the coastal region during the CPE.